Exploring methylene blue as an effective alternative to radiotracer for sentinel lymph node biopsy in early breast cancer in resource-limited settings - Vadodariya, Bhavin P.; Laxmidhar, Murtuza I.; Zope, Anagha; Shah, Shakuntala V. (International Surgery Journal, 2024)
Background: Sentinel lymph node biopsy is the recommended approach in the evaluation of axilla during breast cancer surgery. This study evaluated the results of patients who underwent methylene blue sentinel lymph node biopsy. Methods: The study included 35 female patients with T1, T2 and T3 tumours. 5 ml of 1% methylene blue was injected into the periareolar region. The axillary sentinel lymph node was found and removed, and axillary dissection was performed. The sentinel lymph node and axillary dissection specimen were histopathologically examined, and the results were compared. Results: The sentinel lymph node was found in 33 (90%) patients. There were no complications associated with the use of methylene blue dye. Methylene blue-stained sentinel nodes were histologically negative for malignancy in 42% and positive in 58% of patients. Corresponding to sentinel nodes, the final axillary staging was negative in 60% and positive in 40% of patients. On diagnostic accuracy parameters, the sensitivity of the methylene blue method in early breast cancer (cT1-3N0M0) patients was 90.47%, and the specificity was 100%. The PPV of the technique under study was found to be 100% and NPV was 85.71%. The accuracy rate was 93%, and the false negative rate was identified as 9.5%. Conclusions: Sentinel lymph node biopsy by methylene blue is a method that can be applied with high accuracy. Methylene blue can be considered as an alternative to radio colloid dye in sentinel lymph node biopsy in a limited resource setting.